Estudos citogenéticos clássicos e moleculares em espécies do gênero Harttia (Siluriformes, Loricariidae), com enfoque no papel dos DNAs repetitivos na evolução cariotípica do grupo - Blanco, Daniel Rodrigues (Universidade Federal de São Carlos, 2012)
Among the Siluriformes, the Loricariidae family is the most numerous, containing approximately 800 species distributed in approximately 100 genera (Eschmeyer & Fricke 2012). Loricariidae is subdivided into six subfamilies: Lithogeninae, Neoplecostominae, Hypoptopomatinae, Loricariinae, Delturinae and Hypostominae. Harttia is a small genus of the Loricariinae subfamily that includes the fish popularly known as armored catfish. Members of this subfamily are characterized by a long and depressed caudal peduncle, the absence of adipose fin, caudal fin emarginated and large bony plates surrounding the anal papilla. They inhabit specific regions of the rivers and streams, and form small semi-isolated populations because they have not migratory habits. In this genus are described nineteen species, of which seventeen are allocated in Brazilian basins, however only a few species had been analyzed by cytogenetic methods. Thus this work characterized, by conventional (Giemsa, C-banding and Ag-NOR) and molecular cytogenetics methods (hybridizations with 5S rDNA, 18S rDNA, [GATA]n, [TTAGGG]n, Rex1, Rex3 and Rex6 probes), 7 species of Harttia: H.kronei, H.gracilis, H.longipinna, H punctata, H. loricariformis, H. torrenticola and H. carvalhoi. This paper presents the first chromosomal description for the species: H. gracilis, H. longipinna, H. punctata and H. torrenticola. The chromosome data obtained allowed to infer that the sex chromosome system XX/XY1Y2, found in H. carvalhoi, originated from a centric fission event of a metacentric chromosome formed by a fusion event occurred before the diversification of the clade formed by H. carvalhoi and H. torrenticola. In the chromosomal analysis of a population of H. longipinna was verified up to 2 micro B chromosomes. The data obtained enabled the detection and characterization of the sex chromosome system X1X1X2X2/X1X2Y in H. punctata possibly caused by a translocation event between the first two acrocentric pairs, chromosomes that carrying the 5S and 18S rDNA sites. The hybridizations with the Rex1, Rex3 and Rex6 retroelements showed that these elements are highly dispersed in the genome of the species VIII analyzed, both in heterochromatic regions as euchromatic regions. Although transposable elements are often associated with chromosomal rearrangements due to its ability to move in the genome, for the species of the Harttia, the accumulation of Rex sequences can not be correlated to chromosomal rearrangements. It is likely that these sequences can have an activity in gene regulation since it was found in large quantities in euchromatic regions. The data regarding biological aspects of Harttia allow infer that the restriction of gene flow brought about by isolation of the watersheds may have contributed to the fixation of the chromosomal rearrangements among the analyzed species. The great chromosomal diversity, here represented by: (i) different diploid numbers and karyotype formulas found between different species analyzed, (ii) for the presence of supernumerary chromosomes in H. longipinna and multiple sex chromosomes systems found in H. carvalhoi and H. punctata, (iii) alocation differentiated of the sites of 5S and 18S rDNA, makes the Harttia genus an excellent model for studies of chromosomal evolution.
Keywords: Citogenética de peixes; Cascudo (Peixe); Harttia; DNA repetitivo; CIENCIAS BIOLOGICAS::GENETICA